53.2: Invited Paper: Measurement and Analysis of Current Efficiency of Blue and Green Micro‐LED Arrays with Different LED Chip Sizes. (24th February 2021) - Guo, Enqing; Tian, Wenya; Li, Qing; Wang, Yan; Wang, Chenggong
Abstract : Blue and green InGaN/GaNμLED arrays with different LED chip sizes were fabricated and tested in IVL system. As the chip size reduces, the current density at peak efficiency increases gradually for both blue and green samples. The current efficiency of the smaller μLED is lower than that of the bigger one.